The Effect of High-Intensity Interval Training (HIIT) Program on Increasing 50m Freestyle Sprint Speed in Adolescent Swimmers - Hanafi, Suriah; M. Imran Hasanuddin (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
Improving sprint swimming performance in adolescent athletes is an important concern in the youth sports coaching process. This study aims to determine the effect of the High-Intensity Interval Training (HIIT) training program on the 50-meter freestyle sprint speed in adolescent swimmers. The method used is a quantitative experimental research with a pre-test and post-test control group design, involving 20 athletes divided into two groups: experimental and control. The data collection technique was carried out through a swimming time test before and after the intervention for six weeks, and analyzed using a paired t-test and an independent t-test. The results showed that the experimental group experienced a significant increase in performance compared to the control group, the results of the paired t-test showed a statistical value of t = 42.74 with a significance value of p <0.001. The results of the paired t-test showed a value of t = 18.76 with a significance value of p <0.001. This shows that the HIIT program is effective in increasing sprint speed in adolescent athletes. These findings contribute to the science of sports coaching and physical education by offering an efficient, evidence-based, and applicable training approach in the context of youth athlete coaching. The conclusion of this study confirms that HIIT can be an appropriate alternative strategy for coaches in developing athlete sprint performance. Further research is recommended to explore other technical and physiological variables in more depth.